The role of proprotein convertase subtilisin/kexin type 9 in atherosclerosis - Vekić, Jelena; Bojanin, Dragana; Spasojević-Kalimanovska, Vesna (Biologia Serbica, 2020)
Dyslipidemia is one of the predominant causes of atherosclerosis and cardiovascular disease (CVD) development. Accordingly, lifestyles approaches and therapeutic targeting of low-density lipoprotein (LDL)-cholesterol remain the main strategies for CVD prevention and treatment. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a secretory serin-protease with important roles in lipoprotein metabolism. In particular, PCSK9 promotes degradation of hepatic LDL-receptors, leading to reduced clearance of LDL particles and increased plasma LDL-cholesterol levels. To date, a large body of evidence from experimental, genetic and clinical studies indicates that PCSK9 is implicated in the development of atherosclerosis. As this research is moving forward, additional roles of PCSK9 beyond cholesterol metabolism and atherosclerosis are being discovered. In the present paper, we will discuss our current knowledge of the role of PCSK9 in atherosclerosis and its associations with cardiometabolic risk factors, and provide a brief overview of the recent achievements in pharmacological inhibition of PCSK9-mediated LDL-receptor degradation toward LDL-cholesterol reduction and prevention of CVD development.